Development of Industrial Catering and Its Influence on Changing Climate Conditions - GRISHKINA, Svetlana; BEREZYUK, Valentina; SIDNEVA, Vera; SAFONOVA, Irina; SHCHERBININA, Yulia (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021, 2021)
In a competitive environment, most catering establishments strive for quality food preparation and customer service. The presence of many public catering enterprises on the market forms a high level of competition in this area of economic activity, where recently attention has been focused on environmental factors. In this regard, the development and implementation of an enterprise development strategy is the most important condition for increasing the efficiency of its activities, competitiveness, and sustainability of industrial catering companies.